The Past and Future Time in the Present in 1 John - Merwe, Dirk G. van der (Acta Patristica et Byzantina, 2008)
The reflection on and definition of time in this research have been directed at trying to understand how the author of 1 John used his time references to make sense of his experiences in the Johannine community. The objective in this article is to point out how the author distinguishes between the past, the present and the future and also how closely he has interwoven and blended his perceptions to objectify time. In order to achieve this, the author's point of departure is that Jesus Christ was made the hermeneutical tool that enables us to understand the past, the present and the future of time. Methodologically this paper starts with a comparison between time in antiquity and time in the New Testament, which enables the author to construct a basic framework for the discussion of "time" in the rest of this paper. In the latter part of the paper the investigation of "the past and the future of time in the present in 1 John" is conducted from a sociocultural and a socio-theological perspective on time. A time diagram has been constructed and added in an addendum in order to help to determine the basic content of the investigation.
free